BCR‐ABL1 molecular remission after 90Y‐epratuzumab tetraxetan radioimmunotherapy in CD22+ Ph+ B‐ALL: proof of principle. (12th September 2013) - Chevallier, Patrice; Bodet‐Milin, Caroline; Robillard, Nelly; Eugene, Thomas; Menard, Audrey; Le, Claire; Guillaume, Thierry; Delaunay, Jacques; Escoffre‐Barbe, Martine; Wegener, William A.; Goldenberg, David M.; Kraeber‐Bodéré, Francoise
Abstract Although targeted therapies are used increasingly in hematologic malignancies, we are unaware of any prior studies of radioimmunotherapy (RAIT) in B‐acute lymphoblastic leukemia (ALL), even though this radiosensitive tumor expresses CD22, potentially a good target for this approach. Here, we report a patient with Philadelphia chromosome‐positive B‐ALL in third relapse who received RAIT with 90yttrium (90Y)‐labeled anti‐CD22 epratuzumab tetraxetan. Seven weeks after initiating therapy, the patient achieved a BCR‐ABL1 molecular remission documented by RT‐qPCR, which is now continuing at 6 months while awaiting an allogeneic hematopoietic stem cell transplant. 90Y‐Epratuzumab tetraxetan may be a promising therapeutic option for CD22+ B‐ALL patients.